Assessing and classifying soil for wheat, barley crops and olive trees for the area between Horan valley and Al-Mohammedi valley in the western plateau - Ibrahim, Noor Khalil; Aldulaimi, Saadi abed Awda (Al-Adab Journal, 2021)
The study was carried out to study the types of soil and area of the study in order to evaluate the cultivation of wheat, barley, and olive crops for the better exploitation of the land, and samples were taken for the soil and analysis of chemical properties through nine sections and map them using ARC G.I.S 10.3. Based on the U.S. classification for 2006, The soil was classified as the study area. The study found that the area of the soil of the dry soils (Arridos gypsum, calcareous and sedimentary soils, Alluvial) and using the classification of FAO and based on the proposals prepared in (sys etall 1993) land of study Area. The results showed that the productivity of the land for the wheat crops is good, especially in the areas near the Euphrates River with in piedon (1) was (50.34) of productivity and within piedon (7,5,3) they are rang productivity (22.02,21.65, 24.03) the piedon s were in a weak production category. The yield of barley was medium in piedon (1) with a value of (76.3) in the high productivity category and the piedon (9.8.7.6.3) value (27.31 ,19.06, 24.47, 23.69, 19.17) productivity in piedon (5) was (37.12) with in the category of good productivity While the rest of the piedons were in the category of un productive. As for the olive trees, the results were significantly different. the piedon (1) was (68.67) in the high productivity category and the piedon (6,5) was (22.14) and (22.57) respectively (11.49, 11.03,) in the order in the category of weak productivity, while the rest of piedons have been zero productivity.